2020
DOI: 10.1111/ffe.13217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microstructure of simulated heat‐affected zone on low‐ to high‐cycle fatigue properties of low‐carbon steels

Abstract: To clarify the effect of microstructural changes on the fatigue property of the weld heat-affected zone (HAZ), low-to high-cycle fatigue tests were conducted on 16 types of simulated HAZ specimens that had been prepared using thermal processes. The results showed the fatigue S-N curves of the HAZ to be widely scattered as a function of strength level. These fatigue data were divided into two groups: coarse grain (CG) and fine grain (FG) HAZ, when strain amplitude was used to represent S-N curves. The fatigue d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…One alternative is to use thermal simulation for each sub-HAZ to assess individual performance. 18,19 Although thermal simulation methods have been widely used to study the microstructure and mechanical properties of the HAZ, 20,21 reports on the fatigue performance of the HAZ mainly focused on the properties of the overall welded joint, 22,23 and little work has been done to investigate the fatigue properties of each sub-HAZ in an X80 pipeline, especially in terms of fatigue crack growth. 24 In addition, the performance of ICHAZ has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…One alternative is to use thermal simulation for each sub-HAZ to assess individual performance. 18,19 Although thermal simulation methods have been widely used to study the microstructure and mechanical properties of the HAZ, 20,21 reports on the fatigue performance of the HAZ mainly focused on the properties of the overall welded joint, 22,23 and little work has been done to investigate the fatigue properties of each sub-HAZ in an X80 pipeline, especially in terms of fatigue crack growth. 24 In addition, the performance of ICHAZ has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The same issues were also reported in other studies. [8,10,15,34] Figure 7 shows the crack density as a function of the number of cycles for three different stress amplitudes. The crack density rises in all three cases with increasing number of cycles, indicating an accelerating fatigue damage evolution with increasing N and Δσ/2.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11] The observed slip band formation occurred primarily near and along PAGBs. This result is in good agreement with the studies by Nishikawa et al, Batista et al, and Krupp et al, [10,11,14] which also reported a slip band formation at PAGBs. Apart from PAGBs, block boundaries are also cited as slip band formation sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance testing of each sub-HAZ is hindered due to their small areas. Thermal simulation can be used for each sub-HAZ to test their individual performance 18,19 . Although thermal simulation methods have been widely used to study the microstructure and mechanical properties of the HAZ 20,21 , reports on the fatigue performance of the HAZ mainly focused on the overall weld joint 22,23 .…”
Section: Introductionmentioning
confidence: 99%